Immunoprophylactic potential of recombinant outer membrane protein of Salmonella enterica serovar Typhi against enteric fever in BALB/c mice - Kunza Latif; Shagufta Naz; Imran altaf; Rasheeda Bashir; Faiza Saleem; Neelma Munir; Farheen Aslam (Journal of King Saud University: Science, 2024)
Objectives: This study was design to explore the immunogenic behavior of LamB and SpaO outer membrane protein of Salmonella serovar Typhi against enteric fever in BALB/c mice. Methods: SpaO or LamB genes of locally isolated strain of S.Typhi was amplified, cloned and expressed. Recombinant protein SpaO and LamB were purified and lyophilized to prepare aluminum hydroxide Gel precipitated vaccine. Clinical trials were performed in BALB/c mice. The Immunoprophylactic potential of recombinant SpaO or LamB alone and in combination at different concentrations were determined using Complement fixation test along with whole culture attenuated and commercial vaccine. Results: The immune response of rSpaO and rLamB proteins in combination at 500 µg/ml was significantly high at 48th day and maintained until 60thday. Protective immune potential of recombinant monovalent and multivalent vaccine assessed upon challenge in mice with 109 cells of S.Typhi virulent culture. Out of five, no mice could survive in control group although rSpaO and rLamB in combination at 500 µg/ml conferred 80 % protection. Whereas the monovalent rSpaO and rLamB vaccine elucidate protection 60 % or 40 % respectively. Conclusion: From this study, it is conclude that combine vaccine rSpaO and rLamB effectively enhanced the immunological response and withstand the challenge of the causative agent more effectively as compared to the monovalent vaccines.